The influence of transformational leadership on organizational sustainability in the context of industry 4.0: Mediating role of innovative performance - Aemin Nasir; Nazlina Zakaria; Rushami Zien Yusoff (Cogent Business & Management, 2022)
The current study intends to ascertain the influence of organizational sustainability in the context of Industry 4.0 of textile industry of Pakistan. This study integrates the transformational leadership approach by aligning it with Industry 4.0 in order to manipulate the inequitable sustainability. The sustainability of businesses has dramatically been challenged due to digitalisation, smart manufacturing, and technological advancement issues, so therefore innovation has expanded magnitude in boosting the overall performance. The study determines the influence of transformational leadership, innovative performance on organizational sustainability, particularly in the perspective of Industry 4.0. The study is quantitatively analysed, and data collected from ISO textile firms of Pakistan through questionnaires. The collected data analysed on Smart-PLS through measurement model and structural equation modelling with second stage order. The results seem interesting as the association of Industry 4.0 influences the entire relationship significantly. Under the context of the fourth industrial revolution, the transformational leadership approach has uniquely boosted innovation performance and organizational sustainability simultaneously. The results depicted that innovative performance enhances organizational sustainability more after integration with smart technologies of Industry 4.0. Furthermore, the mediation reportedly confirmed in hypotheses found to be statistically significant. The results of the study are essential for the textile industry to develop strategies towards sustainability concerns while emerging the organization with Industry 4.0 to attain operational innovativeness. The outcomes of the research will work as a guideline for Pakistan's Textile Industry to increase the working efficiency and productivity effectively. The research's framework is a step forward to not only explore future empirical research but also it will help the other manufacturing sector to align the traditional approaches with high technological initiatives to uphold organisational sustainability.
Keywords: 650; fourth industrial revolution; Industry 4.0; innovative performance; organizational sustainability; Transformational leadership